Strategic Competition in Oligopolies with Fluctuating Demand - Neubecker, Leslie (Lecture Notes in Economics and Mathematical Systems,, 2006)
Dynamic oligopolistic competition has implications both for the strategic management of firms and for the design of an effective competition policy. Consequently, the present book considers the issue from a private and social perspective. It discusses the potential pro- and anticollusive effects of long-term business strategies, especially for cooperation and reinvestment in production, financing and management compensation, in markets with fluctuating demand. The method of supergame theory is applied to integrate long-run decisions and different types of demand into the analysis. Aside from its contributions to the theoretical literature, the book provides valuable insights into the design of competition policy. The observed development of prices is an indicator of the extent of collusion in the market and can thereby be used to assess antitrust regulation in certain business areas, and to focus the resources of competition authorities on markets where conditions are conducive to collusion.